The Influence of Promotion Through Social Media on Purchasing Decisions with Trust as a Moderation Variable - Asmin Rahayaan (Journal of Management Research and Studies, 2023)
This research aims to determine the effect of promotions via social media on purchasing decisions with trust as a moderating variable. The sampling technique used in this research is nonprobability sampling with a total of 120 respondents. Research location, namely Meteor Cell in Malang City. The data collection techniques are documentation, questionnaires and observation, the information used is secondary and primary. And the data is processed through SmartPLS 4 software. The results of this research show that, 1). Promotion via social media has a positive and significant effect on purchasing decisions at Meteor Cell, Malang City. 2). Trust has a positive and significant effect on purchasing decisions at Meteor Cell, Malang City. 3). Trust is able to act as a strong mediator in the influence of promotion via social media on purchasing decisions at Meteor Cell, Malang City.